2020
DOI: 10.3389/fnut.2020.604328
|View full text |Cite
|
Sign up to set email alerts
|

Holly (Ilex latifolia Thunb.) Polyphenols Extracts Alleviate Hepatic Damage by Regulating Ferroptosis Following Diquat Challenge in a Piglet Model

Abstract: Background: Holly (Ilex latifolia Thunb.) polyphenols extracts (HPE) contain high amounts of polyphenols, including phenolic acids, triterpenoids, tannic acids, and so on, which have strong antioxidant function. This experiment was aimed to explore the protective effect and mechanism of HPE against hepatic injury induced by diquat.Methods: Thirty-two weaned piglets were allotted by a 2 × 2 factorial experiment design with diet type (basal diet vs. HPE diet) and diquat challenge (saline vs. diquat). On the 21st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Earlier work has demonstrated that iron, a major component of haemoglobin, which is extremely toxic to nerve cells, is liberated during haematoma formation following ICH and can initiate a Fenton reaction. The latter leads to the generation of multiple hydroxyl radicals, which stimulate and exacerbate tissue oxidation which harms cellular membranes, DNA and proteins and gives rise to nerve cell ferroptosis (Li et al 2017a, b, c;He et al 2020;Magtanong and Dixon 2018;Zhang et al 2018a, b;Djulbegovic and Uversky 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work has demonstrated that iron, a major component of haemoglobin, which is extremely toxic to nerve cells, is liberated during haematoma formation following ICH and can initiate a Fenton reaction. The latter leads to the generation of multiple hydroxyl radicals, which stimulate and exacerbate tissue oxidation which harms cellular membranes, DNA and proteins and gives rise to nerve cell ferroptosis (Li et al 2017a, b, c;He et al 2020;Magtanong and Dixon 2018;Zhang et al 2018a, b;Djulbegovic and Uversky 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The hepatocytes ultrastructure were observed and photographed with a HT7700 TEM (Hitachi Co. Ltd., Tokyo, Japan) referred to previous study [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other polyphenol-containing food additives have been assessed for their ability to reduce oxidative stress and inflammation. For example, holly tree derived polyphenol extracts were associated with improved liver function in weaned piglets challenged with oxidative stress using diquat, as evident from heightened anti-oxidant capacity, and expression of metabolic transferases and ferroptosis mediators in the liver [ 228 ]. Resveratrol (a stilbene common to berries) added to diets reduced Salmonella and E. coli counts in the fecal content of pathogen challenged weaned piglets, additionally increasing serum immunoglobin G (IgG), reducing TNF-α levels, and appearing to improve the gut microenvironment in general due to improvements in nitrogen digestibility [ 229 ].…”
Section: Health Effects Of Dietary Polyphenols In Pigs and Other Animalsmentioning
confidence: 99%